Assessment of tropospheric CALIPSO Version 4.2 aerosol types over the ocean using independent CALIPSO–SODA lidar ratios - Z. Li; Z. Li; D. Painemal; D. Painemal; G. Schuster; M. Clayton; M. Clayton; R. Ferrare; M. Vaughan; D. Josset; J. Kar; J. Kar; et al. (Atmospheric Measurement Techniques, 2022)
We assess the CALIPSO Version 4.2 (V4) aerosol typing and assigned lidar ratios over ocean using aerosol optical depth (AOD) retrievals from the Synergized Optical Depth of Aerosols (SODA) algorithm and retrieved columnar lidar ratio estimated by combining SODA AOD and CALIPSO attenuated backscatter (CALIPSO–SODA). Six aerosol types – clean marine, dusty marine, dust, polluted continental/smoke, polluted dust, and elevated smoke – are characterized using CALIPSO–SODA over ocean and the results are compared against the prescribed V4 lidar ratios, when only one aerosol type is present in the atmospheric column. For samples detected at 5 or 20 km spatial resolutions and having AOD > 0.05, the CALIPSO–SODA lidar ratios are significantly different between different aerosol types, and are consistent with the type-specific values assigned in V4 to within 10 sr (except for polluted continental/smoke). This implies that the CALIPSO classification scheme generally categorizes specific aerosols types correctly over regions where they are abundant. We find remarkable daytime/nighttime regional agreement for clean marine aerosol over the open ocean (CALIPSO–SODA = 20–25 sr, V4 = 23 sr), elevated smoke over the southeast Atlantic (CALIPSO–SODA = 65–75 sr, V4 = 70 sr), and dust over the subtropical Atlantic adjacent to the African continent (CALIPSO–SODA = 40–50 sr, V4 = 44 sr). In contrast, daytime polluted continental/smoke lidar ratio is more than 20 sr smaller than the constant V4 value for that type, attributed in part to the challenge of classifying tenuous aerosol with low signal-to-noise ratio. Dust over most of the Atlantic Ocean features CALIPSO–SODA lidar ratios less than 40 sr, possibly suggesting the presence of dust mixed with marine aerosols or lidar ratio values that depend on source and evolution of the aerosol plume. The new dusty marine type introduced in V4 features similar magnitudes and spatial distribution as its clean marine counterpart with lidar ratio differences of less than 3 sr, and nearly identical values over the open ocean, implying that some modification of the classification scheme for the marine subtypes is warranted.